Pengaruh Kompensasi Terhadap Retensi Karyawan Pada Perusahaan Rokok Makmur Rotama Manonjaya Kabupaten Tasikmalaya - Serli Herawati; Rudi Setiawan; Iis Miati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study was conducted to examine the extent to which compensation influences employee retention at PR. Makmur Rotama, Tasikmalaya Regency. In the context of Human Resource Management, compensation is considered a crucial factor that can encourage employees to remain with the company. A high rate of employee turnover may reduce operational efficiency and productivity; therefore, organizations need to design fair and competitive reward systems to maintain workforce stability. This research applied a quantitative approach involving two primary variables: compensation as the independent variable (X) and employee retention as the dependent variable (Y). The population consisted of 90 employees, and the sample was selected using a random sampling technique. Data were collected through questionnaires, direct observation, interviews, and supporting documentation. Data analysis procedures included validity and reliability testing of the instruments, simple linear regression analysis, calculation of the coefficient of determination, and a t-test to determine the significance of the effect. The findings indicate that compensation contributes 15.1% to employee retention, while the remaining 84.9% is influenced by other factors beyond the scope of this study. Thus, compensation has a positive effect on employee retention, although it is not the sole determining factor.